Improved patient-specific hyperthermia planning based on parametrized electromagnetic and thermal models for the SIGMA-30 applicator. (1st January 2021) - Nadobny, Jacek; Lim, Amanda; Seifert, Georg; Sullivan, Dennis; Chrzon, Benjamin; Weihrauch, Mirko; Zschaeck, Sebastian; Herz, Enrico; Moczynska, Aleksandra; Pellicer-Guridi, Ruben; Wust, Peter; Beck, Marcus; et al.
Abstract: Objective: To create an improved planning method for pediatric regional hyperthermia (RHT) using the SIGMA-30 applicator (SIGMA-30). Materials and Methods: An electromagnetic model of SIGMA-30 was generated for use with the finite-difference time-domain (FDTD) method. Applying special MATLAB-based algorithms, voxel models of a pediatric patient with pelvic rhabdomyosarcoma were created from Computed-Tomography (CT) contours for use with the FDTD method and the finite-difference (FD) method capable of using either temperature-independent or temperature-dependent perfusion models for solving the Bioheat Transfer Equation (BHTE). Patient models were parametrized regarding, first, the positioning in the applicator, second, the absorbed power range and, third, different perfusion models, resulting in the so-called Parametrized Treatment Models (PTMs). A novel dedicated optimization procedure was developed based on quantitative comparison of numerical calculations against temperature and power measurements from two RHT therapies. Results: Using measured data, a realistic absorbed power range in the patient model was estimated. Within this range, several FDTD and BHTE runs were performed and, applying the aforementioned optimization scheme, the best PTMs and perfusion models were identified for each therapy via a retrospective comparison with measurements in 14 temperature sensor positions: 5 in the tumor, 8 in rectum and one in bladder. Conclusion: A novel dedicated optimization procedure for identification of suitable patient-specific electromagnetic and thermal models, which can be used for improved patient planning, was developed and evaluated by comparison with treatment-derived measurements using SIGMA-30. The optimization procedure can be extended to other hyperthermia applicators and to other patient types, including adults.